Estudo do papel do sistema purinérgico na mediação das respostas cardiovasculares do núcleo ambíguo e do reflexo bezold-jarisch em ratos anestesiados - Passamani, Luciana Mesquita (2009)
The purine nucleotide adenosine 5’-triphosphate (ATP) may act as a neurotransmitter/neuromodulator in the central nervous system, including nuclei associated with autonomic control. Anatomical studies have demonstrated the existence of P2 receptors in the nucleus ambiguus (NA). However, very little is known about the role of these receptors in mediating the cardiovascular responses of the NA. Therefore, the aims of our study were: a) to evaluate the effects on blood pressure and heart rate of the activation of purinoceptors in the NA, b) to evaluate the effects of the autonomic blockade on the cardiovascular responses due to the activation of purinoceptors in the NA, c) to evaluate if the purinoceptors modulate the cardiovascular responses due to glutamatergic activation of the NA, and d) to evaluate the role of the purinergic system at the level of the NA in mediating the cardiovascular responses of the Bezold-Jarish reflex. This study used anesthetized (urethane, 1.4 g/kg, i.p.) Wistar rats blocked with succinylcholine and artificially ventilated. The femoral artery and vein were catheterized to allow cardiovascular recordings and drugs injections, respectively. The stereotaxic coordinates used to reach the NA were: +0.5 mm rostral to obex, ±1.7 mm lateral and -1.2 to -1.8 mm ventral. The following drugs were used: L-Glutamate (5.0 nmol/50 nL), ATP (0.31; 2.5; 3.5; 5.0; 6.0 nmol/50 nL), prazosin (1.0 mg/kg), methyl-atropine (2.0 mg/kg), PPADS (500 pmol/100 nL) and saline (0.9%). The Bezold-Jarish reflex was activated by the intravenous injection of phenylbiguanide (12.0 µg/kg). Our data showed dosedependent bradycardic responses and also pressor responses to the ATP microinjection in the NA with the doses tested (0.31; 2.5; 3.5; 5.0; 6.0 nmol/50 nL). The α1-adrenergic blockade with prazosin did not change the bradycardic response but abolished the pressor response to the ATP (3.5 nmol/50 nL) microinjection in the NA. The muscarinic blockade with methyl-atropine abolished the bradycardic response induced by the ATP (3.5 nmol/50 nL). Ipsilateral microinjection of PPADS (500 pmol/100 nL) in the NA significantly attenuated the bradycardia but did not affect the pressor response to the ATP (3.5 nmol/50 nL) in the NA. Moreover, ipsilateral microinjection of PPADS (500 pmol/100 nL) in the NA significantly attenuated the bradicardic response to LGlutamate (5.0 nmol/50 nL) microinjection into the NA. Bilateral microinjections of PPADS in the NA significantly attenuated the depressor and bradycardic responses due to the Bezold-Jarisch reflex activation. These results suggest that the P2 purinoceptors seem to be involved in the mediation of the cardiovagal responses of the NA and that this effect might involve a neuromodulation of the glutamatergic system at the level of the NA in anesthetized rats. Additionally, our data show that the purinoceptors of the NA, seem to participate in the mediation of the cardiovascular responses of the Bezold-Jarish reflex. However, the specific subtypes of purinergic receptors involved in these responses as well as the participation of the purinergic system in other cardiovascular reflexes at the level of the NA, remain to be elucidated.